2014
DOI: 10.1016/j.tra.2014.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts between utility maximisation and regret minimisation in the presence of opt out alternatives

Abstract: An increasing number of studies of choice behaviour are looking at random regret minimisation (RRM) as an alternative to the well established random utility maximisation (RUM) framework. Empirical evidence tends to show small differences in performance between the two approaches, with the implied preference between the models being dataset specific. In the present paper, we discuss how in the context of choice tasks involving an opt out alternative, the differences are potentially more clear cut. Specifically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 16 publications
(26 reference statements)
1
23
0
Order By: Relevance
“…For each model, a constant was specified to be associated with the option to delay care (e.g. Cheng et al, 2012;Hess et al, 2014) . All attribute levels and the constant were included as random parameters, and the individual preference weights were assumed to follow a normal distribution.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…For each model, a constant was specified to be associated with the option to delay care (e.g. Cheng et al, 2012;Hess et al, 2014) . All attribute levels and the constant were included as random parameters, and the individual preference weights were assumed to follow a normal distribution.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…Comparisons between the RUM model and RRM model have been performed many times. According to the literature statistics [24][25][26], research studies on the RRM model increased rapidly from 2010, most of which used stated preference (SP) data to estimate the parameters, and compared these with the MNL model under various choice contexts. Empirical evidence showed that although differences in model fit and predictive performance between the RUM and RRM models may not be significantly distinguished, the policy implications may vary a lot between these two models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this regard, the individuals were asked to choose between two unlabelled hypothetical alternatives, having also the choice of stating their indifference among both alternatives. All experiments considered the same attributes: fare (P), travel time (TT), access time (AT) and 6 As we are considering a binary choice situation in this specific case, it would have been possible to test the approach put forward by Hess et al (2014) by assuming regret minimization. Nevertheless, such comparison would be spurious as we assumed utility maximization when constructing the simulated dataset; the same applies (though to a lesser extent) to alternatives methods, such as the MPD-approach (Cantillo et al, 2010).…”
Section: Real Dataset: Binary Choicesmentioning
confidence: 99%
“…For illustrative purposes, this time we also included a model considering a null-alternative in the context of a regret minimization framework (Model 5). In this case, the additional alternative, can be framed as indifference (Hess et al, 2014). 7 The results are presented in Table 3.2.…”
Section: Real Dataset: Binary Choicesmentioning
confidence: 99%